ANALISIS ALOKASI PENGELUARAN RUMAH TANGGA PETANI KARET DI KECAMATAN BAJUBANG KABUPATEN BATANGHARI - Elwamendri; Jannah, Raudhatul; Saputra, Ardhiyan (JALOW | Journal of Agribusiness and Local Wisdom, 2021)
Household Expenditure Allocation consists of various expenditures that form a pattern in which many factors influence it. This research was aimed to analyze (1) farmer household social economic characteristics and patterns of household expenditure rubber farmers in Bajubang Sub-district. (2) factors affecting household expenditure of rubber farmers in Bajubang Sub-district. The data were analyzed in descriptive method, tabulation and simultaneous equations model by the method of Two Stage Least Squares (2SLS). Sampling was done by simple random sampling method. The results showed that the age of farmers in Bajubang Sub-district was in productive age with low average education level and sufficient experience in rubber farming with farmers owning an area of ​​2.5 ha. Total household expenditure of rubber farmers is 98.6 percent of total revenue, which consists of total consumption of 83.5 percent and investment of 14.9 percent. The cost of farm production and land area have a positive effect on production. Non-food expenditure and the number of family members have a positive effect on food consumption. Total household income has a positive effect on non-food consumption. Total household income and the number of family members have a positive effect on health investment, while health investment and number of school children have a positive effect on education investment.